Sharia Financing Analysis On The Financial Performance Sharia Banking In The Moderation Of The Syariah Supervisory Board (DPS) - osmad - muthaher (Tirtayasa Ekonomika, 2022)
The aim of this study is to research and examine the effect of Mudharaba, Musyaraka, Murabaha financing on sharia financial performance moderated by sharia supervisory board on sharia bankings in Indonesia during 2013-2016. This study employed descriptive quantitative method by using secondary data i.e. data of Financing, and Return on Asset of sharia banking companies in the period of 2013-2016. The samples were reports published continuously from 2013 to 2016 and financial statements which have complete data based on researched variables derived through purposive sampling. To analyze the data, this study used some tests of multiple linear regression, classical assumption, and hypotheses test which included coefficient determination test of R2, F test, and t test. Based on the data analysis, it can be concluded that the factors that affect sharia financial performance (ROA) included Mudharaba, Musharaka and Murabaha financing, where all independent variables have significant effect on ROA. While DPS has been successful in moderating the correlation of mudharaba and Musyarakah variable and ROA but DPS has not been successful in moderating the correlation of Murabah and ROA